Implementasi Peer-Assessment sebagai Salah Satu Teknik Penilaian Profil Pelajar Pancasila - Adawiyah, Siti Rabiatul (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2023)
One of the characteristics that distinguishes the independent curriculum from previous curricula is the profile of Pancasila students as the main goal (aim) of national education. The Pancasila student profile contains the characters and competencies needed by Indonesian citizens to be good citizens of the world. Therefore, it is the teacher's job to ensure that this profile has developed in a balanced way in each student. Assessment is a method used to find out the development of the Pancasila student profile and continuous assessment is absolutely necessary in order to get a clear picture. One of the assessment techniques that can be used is peer-assessment, because with this assessment there is more time to carry out the assessment than if only the teacher did the assessment. This study aims to provide a theoretical study of the implementation of peer-assessment as a technique for assessing Pancasila student profiles. This research is a library research. Researchers obtained data by conducting literature reviews from various sources, such as: books, journals, scientific papers, as well as other relevant documents and literature.